Pretreatment blood biomarkers combined with magnetic resonance imaging predict responses to neoadjuvant chemoradiotherapy in locally advanced rectal cancer - Shi, Xinyu; Zhao, Min; Shi, Bo; Chen, Guoliang; Yao, Huihui; Chen, Junjie; Wan, Daiwei; Gu, Wen; He, Songbing (Frontiers in Oncology, 2022)
Aim: To investigate the value of pretreatment blood biomarkers combined with magnetic resonance imaging (MRI) in predicting the efficacy of neoadjuvant chemoradiotherapy (NCRT) in patients with locally advanced rectal cancer (LARC). Methods: This study involved patients with LARC who received NCRT and subsequently underwent total mesenteric excision from June 2015 to June 2021 at the First Affiliated Hospital of Soochow University. Patients with incomplete courses of neoadjuvant therapy, comorbidities with other malignancies or diseases that affect the study outcome, and those who underwent unplanned surgery were ultimately excluded. Laboratory data such as albumin, CEA, various blood cell levels, and MRI related data such as tumor regression grade assessed by magnetic resonance imaging (mrTRG) were collected from the included patients one week prior to NCRT. MrTRG is a common clinical imaging metric used to assess the degree of tumor regression in rectal cancer, primarily based on morphological assessment of residual tumor. Furthermore, pretreatment blood biomarkers such as neutrophil to lymphocyte ratio (NLR), lymphocyte to monocyte ratio (LMR), albumin to fibrinogen ratio (AFR), and prealbumin to fibrinogen ratio (PFR) were assessed. The independent variables for pathologic complete response (pCR) to NCRT were determined by univariate and multivariate logistic regression analyses. Receiver operating characteristic (ROC) curve analysis was used to examine the performance of MRI with or without pretreatment blood biomarkers in predicting pCR using DeLong's method. A nomogram was created and confirmed internally. Results: Fifty-nine individuals with LARC satisfied the inclusion criteria, among which 23 showed pCR after NCRT. Logistic regression analysis demonstrated that pretreatment CEA (≤ 3 µg/L, OR = 0.151, P = 0.039), NLR (OR = 4.205, P = 0.027), LMR (OR = 0.447, P = 0.034), and PFR (OR = 0.940, P = 0.013) were independent predictors of pCR to NCRT. The AUCs of mrTRG alone and mrTRG plus the above four pretreatment blood biomarkers were 0.721 (P =0.0003) and 0.913 (P <0.0001), respectively. The constructed nomogram showed a C-index of 0.914. Conclusion: Pretreatment blood biomarkers combined with MRI can help clinical efforts by better predicting the efficacy of NCRT in patients with locally advanced rectal cancer.